Beyond the Line : Military and Veteran Health Research - Alice B. Aiken (editor), Stéphanie A. H. Bélanger (editor) (McGill-Queen's University Press, 2013)
This collective brings together some of the different research challenges that have been undertaken by researchers from across Canada on the topic of military and veteran health. The researchers who contributed to this volume were part of the third Military and Veteran Health Research (mvhr) Forum that took place in November 2012, hosted by Queen’s University and the Royal Military College of Canada in Kingston, Ontario, under the auspices of the Canadian Institute for Military and Veteran Health Research (cimvhr)